1) rozwiąż równania:
a)x+15=8 ⅓
b)12,4-x=20
c)2x+5=15¾
d)-3x-x=20
e)2(3x-4)=10
f)-3(5+2x)=15
g)4(x+3)-2=-6
h)30-10(2-3x)=-50
2) rozwiąż równania
a)6x-7(11+2x)+2=-4(15-x)+3x
b)3(5x+3)=7(x+5)-3(2-x)
c)2(x-1)+4(x-3)=-3(x-2)+9x
d)5x-3(6-8x)=x-7(x+4)
e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
f)3(2x+3)-5(x-2)-4(x+7)=3
g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
Bardzo proszę o pomoc w rozwiązaniu- najlepsze nagradzam:)

3

Odpowiedzi

2009-12-03T12:47:34+01:00
A)x+15=8 ⅓ |*3
3x+45=8 |-45
2x=-37
x=-18,5

b)12,4-x=20 |-12,4
-x=7,6
x=-7,6

c)2x+5=15¾ |*4
8x+20=63 |-20
8x=43
x=5 3/8

d)-3x-x=20
-4x=20
x=-5

e)2(3x-4)=10
6x-8=10 |+8
6x=18
x=3

f)-3(5+2x)=15
-15-6x=15 |+15
-6x=30
x=-5

g)4(x+3)-2=-6
4x+12-2=-6
4x+10=-6 |-10
4x=-16
x=-4

h)30-10(2-3x)=-50
30-20+30x=-50
10+30x=-50 |-10
30x=-60
x=-2

2) rozwiąż równania
a)6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
-8x-75=-60x+7x |+8x
-75=-60+15x |+60
-15=15x
x=-1


b)3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x+9=10x+29 |-9
15x=10x+20 |-10x
5x=20
x=4

c)2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x+6+9x
6x-14=6x+6 |+14
6x=6x+20 |-6x
0≠20

d)5x-3(6-8x)=x-7(x+4)
5x-18+24x=x-7x-28
29x-28=-6x-28 |+6x
35x-28=-28 |+28
35x=0
x=0

e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
2x+16x-24-6x+18=15x+5+2x-11
12x-6=17x-6 |+6
12x≠17x

f)3(2x+3)-5(x-2)-4(x+7)=3
6x+9-5x+10-4x-28=3
-3x-9=3 |+9
-3x=12
x=-4

g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
21-7,2x=-17,2x+6 |+17,2
21+10x=6 |-21
10x=-15
x=-1,5
3 4 3
Najlepsza Odpowiedź!
2009-12-03T13:03:02+01:00
X+15=8, 1/3
x=8,1/3-15
x=6,2/3

12,4-x=20
x=12,4-20
x=-7,6

c)2x+5=15¾
2x=15,3/4-5
2x=10,3/4
x=(10,3/4):2
x=(43/4)*(1/2)
x=43/8

d)-3x-x=20
-4x=20
x=-5

e)2(3x-4)=10
6x-8=10
6x=10+8
6x=18
x=3

f)-3(5+2x)=15
-15-6x=15
-6x=30
x=-5

g)4(x+3)-2=-6
4x+12-2=-6
4x=-6+2-12
4x=-16
x=-4

h)30-10(2-3x)=-50
30-20+30x=-50
30x=-50-30+20
30x=-60
x=-2

a)6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=-60-2+77
-15x=15
x=-1

b)3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x-7x-3x=35-6-9
5x=20
x=4


c)2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x+6+9x
2x+4x+3x-9x=6+12+2
0x=20
nie dzielimy przez 0

d)5x-3(6-8x)=x-7(x+4)
5x-18+24x=x-7x-28
5x+24x-x+7x=-28+18
35x=-10
x=-10/35
x=-2/7


e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
2x+16x-24-6x+18=15x+5+2x-11
2x+16x-6x-15x-2x=5-11-18+24
-3x=0
x=0

f)3(2x+3)-5(x-2)-4(x+7)=3
6x+9-5x+10-4x-28=3
6x-5x-4x=3+28-10-9
-3x=12
x=-4


g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
-7,2x+17,5x-0,3x=6-21
10x=-15
x=-1,5
3 4 3
2009-12-03T13:20:10+01:00
A)x+15=8 ⅓ /-15
x= 8 i 1/3-15
x= 25/3 - 45/3
x= -6 i 2/3
b)12,4-x=20 /-12,4
x= -7,6
c)2x+5=15¾ /-5
2x= 10 i 3/4 /2
x= 43/8
x= 5 i 3/8
d)-3x-x=20
-4x=20 /4
-x=5
x=-5
e)2(3x-4)=10
6x-8=10 /+8
6x=18 /:6
x=3
f)-3(5+2x)=15
-15-6x=15 /+15
-6x=30 /:6
-x=5
x=-5
g)4(x+3)-2=-6
4x+12-2=-6
4x+10=-6 /-10
4x=-16 /:4
x=-4
h)30-10(2-3x)=-50
30-20-30x=-50
50-30x=-50 /-50
-30x=-100 /:30
x=3(3)
2) rozwiąż równania
a)6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60-4x+3
-8x-75=-57-4x /+75,+4x
-4x=18 /:4
x=-4,5
b)3(5x+3)=7(x+5)-3(2-x)
15x+9= 7x+35-6-3x
15x+9=4x+29 /-4x,-9
11x=20 /:11
x=1(81)
c)2(x-1)+4(x-3)=-3(x-2)+9x
2x-2+4x-12=-3x-6+9x
6x-14=6x-6 /-6x,+14
0x=8
d)5x-3(6-8x)=x-7(x+4)
5x-18-24x=x-7x-28
-19x-18=-6x-28 /+19x,+28
10=13x /:13
x=w zaokragleniu 0,769
e)2x+8(2x-3)-6(x-3)=5(3x+1)+2x-11
2x+16x-24-6x-18=15x+5+2x-11
12x-42=17x-6 /-12x,+6
-36=5x /:5
x=-7,2
f)3(2x+3)-5(x-2)-4(x+7)=3
6x+9-5x-10-4x-28=3
-3x-29=3 /+29
-3x=32 /:3
x=-10(6)
g)6(3,5-1,2x)=5(-3,5x+1,2)+0,3x
21-7,2x=-17,5x+6+0,3x
21-7,2x=-17,2x+6 /-21,+17,2
10x=-15 /:10
x=-1,5
1 5 1